2009
DOI: 10.1590/s0103-97332009000100002
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons between two wavelet functions in extracting coherent structures from solar wind time series

Abstract: Nowadays, wavelet analysis of turbulent flows have become increasingly popular. However, the study of geometric characteristics from wavelet functions is still poorly explored. In this work we compare the performance of two wavelet functions in extracting the coherent structures from solar wind velocity time series. The data series are from years 1996 to 2002 (except 1998 and 1999). The wavelet algorithm decomposes the annual time-series in two components: the coherent part and non-coherent one, using the daub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 17 publications
(21 reference statements)
2
10
0
Order By: Relevance
“…First, we use the WT to remove the long-term trend from the time series, and second, we use the WT to perform the cross-wavelet spectrum (XWS) analysis between two time series. For more details of the first approach, see Bolzan et al (2009). For the second approach the following must be valid: if X(t) and Y (t) are time series and if W X (a, b), W Y (a, b) are their WT, the XWS analysis (Torrence and Compo, 1998;Bolzan and Vieira, 2006) is given by…”
Section: Wavelet and Cross-wavelet Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…First, we use the WT to remove the long-term trend from the time series, and second, we use the WT to perform the cross-wavelet spectrum (XWS) analysis between two time series. For more details of the first approach, see Bolzan et al (2009). For the second approach the following must be valid: if X(t) and Y (t) are time series and if W X (a, b), W Y (a, b) are their WT, the XWS analysis (Torrence and Compo, 1998;Bolzan and Vieira, 2006) is given by…”
Section: Wavelet and Cross-wavelet Analysismentioning
confidence: 99%
“…Indeed, different wavelet functions cause different behavior on the white noise and red noise present in different time series. Bolzan et al (2009), using two kinds of wavelet function in order to extract the CSs, have shown that each wavelet has a different performance due to its mathematical shape. Thus it is possible to assess how different wavelet functions when applied to the same observation data, and taking into account the noise, may lead to different results.…”
Section: Test Of Red Noise and White Noise Effectsmentioning
confidence: 99%
“…Multi-sensory interaction in dynamic driving simulator. Equation (27) calculates the total sensed roll jerk at cabin (vehicle) level. This level signifies the vehicle dynamics model that moves in the visual environment during the simulator drive experiments.…”
Section: Resultsmentioning
confidence: 99%
“…The wavelet transform is used as a mathematical instrument in order to analyze any non-stationary time series, showing the temporal variability of the PSD [27].…”
Section: Data Denoisingmentioning
confidence: 99%
“…However, considering a common physical process, its statistical characteristics related to the pattern of variability should not vary significantly. Moreover, we consider the present analysis a complementary one of those events with which we had earlier work (Bolzan et al, 2005a(Bolzan et al, , 2009bSahai et al, 2005).…”
Section: Introductionmentioning
confidence: 99%